Cloud architecture for analyzing real-time road traffic data - Davidović, Boban; Barać, Dušan (E-business technologies conference proceedings, 2021)
With the expanded usage of IoT sensors in road traffic and an increasing number of vehicles on the road, analyzing road traffic data is something to be considered. Road traffic data is collected using IoT devices and these datasets are massive. Road traffic can be optimized in many ways by making the traffic flow better and ”smarter”. The main goal of this research is to architect a model which will provide a connection between road traffic sensors and traffic participants to build a centralized community where road traffic data can be collected and analyzed in real-time. The goal is to design a cloud architecture that provides an available, scalable, and reliable service that can collect road traffic data, analyze it and provide real-time results.